EFFECT OF EMPLOYEE ENGAGEMENT ON MARKETING STRATEGY IN SERVICE FIRMS IN OGUN STATE NIGERIA - Ogunsola, Olanrewaju Kazeem; Arikewuyo, Kareem Abidemi; Popoola, Claudius Sunday (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2025)
This paper examined the effect of employee engagement on marketing strategy amongst service firms in Ogun State, Nigeria. The targeted population for the study consists of marketing managers, HR heads, and senior managers. Building on Khan's (1990) theory of employee engagement, three dimensions - employee empowerment [Emp_E], employee advocacy [Emp_A], and employee knowledge [Emp_K] - were used to profile employee engagement. Cochran's (1997) finite sample size determination was adopted. Using a simple random technique, electronic closed-ended questionnaires were administered to solicit responses from 333 respondents. The line of best fit model was analyzed with standardized multiple regression analysis (SMRA). Findings revealed that the predictor constructs (Emp_E, Emp_A, and Emp_K) explained 72.9% of the outcome construct (Mkt_S) such that adjusted R2 = .729, F(3, 301) = 273.901, p < 0.001. However, an independent analysis of the predictor constructs revealed that only Emp_E (β1= .613, p <0.001) and Emp_K (β3= .432, p <0.001) have a significant positive relationship with Mkt_S. Evidence shows that Emp_A (β2 = 0.089, p = 0.079) has a positive relationship, but it does not make a statistically significant contribution to the marketing strategy. This insignificant contribution may be due to existing literature which argues that Emp_A is a form of organizational citizenship behaviour which is not directly called on or explicitly rewarded by organizations. Overall, since the regression line is statistically significant, this study submits that there is a significant positive relationship between employee engagement and marketing strategy. This study contributes in two ways. First, it expands Kahn’s theory of employee engagement. Second, it informs marketing managers / HR heads on the importance of designing an inclusive employee growth-oriented program that will facilitate the successful implementation of the marketing strategy. The study recommends that service firms need a strong understanding of key drivers or underlying mechanisms that can facilitate advocacy behaviours in employees. This study used a cross-sectional data approach, which may have biased the results. Hence, the identification of future areas of research has been highlighted.